The effects on Apgar scores and neonatal outcomes of switching from a combination of phenylephrine and ephedrine to phenylephrine alone as a prophylactic vasopressor during spinal anesthesia for cesarean section - Joo Yeon Jeon (Korean Journal of Anesthesiology, 2014)
BackgroundEphedrine, unlike phenylephrine, has a dose-related propensity to depress fetal pH during spinal anesthesia during cesarean section. A low arterial umbilical cord pH has a strong association with neonatal mortality and morbidity. The purpose of this retrospective study was to investigate influences of vasopressor change on Apgar scores and adverse neonatal outcomes in cesarean section.MethodsIn obstetric anesthesia, we changed the prophylactic vasopressor from a combination of phenylephrine and ephedrine to phenylephrine alone in 2000. We evaluated the impact of vasopressor change on Apgar scores (1 and 5 min), incidence of Apgar score < 7 (1 and 5 min), neonatal seizure, continuous positive airway pressure (CPAP), intermittent positive pressure ventilation (IPPV), intraventricular hemorrhage (IVH), periventricular leucomalacia (PVL), and hypoxic ischemic encephalopathy (HIE) in low-risk elective cesarean sections during a period when the combination of phenylephrine and ephedrine was used (2008-2009, two years) and the period of phenylephrine use alone (2011-2012, two years).ResultsThere were no differences in Apgar scores (1 and 5 min), the incidence of 5 min Apgar score < 7, neonatal seizure, CPAP, IPPV, IVH, PVL, and HIE between the two time periods. However, the incidence of 1 min Apgar < 7 was decreased during the period of phenylephrine use compared with the period of phenylephrine and ephedrine use (P = 0.002).ConclusionsConversion from a combination of phenylephrine and ephedrine to phenylephrine alone as a prophylactic anti-hypotensive drug during spinal anesthesia for cesarean section in low-risk pregnancy may be associated with a significant decrease in the incidence of 1 min Apgar < 7.